Al-Tabari's sources on his history of the reign of Caliph Muawiya bin Abi Sufyan (41 AH / 661 AD - 60 AH / 679 AD) - Yousif Al-Mirani, Falah (Humanities Journal of University of Zakho, 2021)
In his talk about the reign of the first caliphs of the Umayyad state, Muawiya bin Abi Sufyan, al-Tabari presented many news, and dealt with mentioning many important historical incidents that the history of that period witnessed, starting from the year (41 AH / 661 AD), And it is known among Muslims as the year of the (Al-jamaea) that witnessed the reconciliation between Imam Al-Hassan bin Ali and Muawiyah bin Abi Sufyan. Passing by mentioning other politically important incidents such as the news of the governors in their states, and the news of the Kharijites and other opponents of the Umayyad rule, as well as mentioning the news of wars and invasions that Muslims fought at home and abroad, And concluding by talking about the death of Muawiyah bin Abi Sufyan in the year (60 AH / 679 CE) and talking about some of his qualities and attributes, Al-Tabari followed the style of the annual history in mentioning the incidents of this period, which is his usual method in his history in general, and the news of political incidents was of the majority, This is natural, given that it witnessed the end of an era and the beginning of a new era in the lives of Muslims. With regard to al-Tabari’s sources on the history of these, they varied between personal sources, and they are the people whom al-Tabari narrated and mentioned in the chains of his chain of transmission for each novel. And among the documents, such as the letters exchanged between prominent personalities during that period, Al-Tabari mentioned many of them in their full texts, and only mentioned others with reference only. Examples include the speeches delivered by some of the participants in political and religious incidents, many of which were mentioned in their full texts, and others were only mentioned briefly or with reference, In addition to wills, as well as lists of some names of some of the participants in the political events of that period, Al-Tabari also relied on his sources on many poems and poetic verses, in addition to his personal data through his prior knowledge of the history of that important period of Muslim history.